Isolation and Diagnosis of Aerobic Bacteria from Patients with Respiratory Tract Infection and Partial Characterization of Their Plasmid Profile - Ahmed, Khalid Daham; Salim, Rawaa Jaji (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this study, the bacteria from sputum specimens of patients with respiratory tract infections were isolated in IbnSina Teaching Hospital, Mosul city, Iraq. The bacteria were subjected to phenotypic and biochemical tests necessary for identification. Twenty five isolates of six different bacterial species were obtained, they are : Staphylococcus aureus, Streptococcus pneumonia, Moraxella cattarhalis, Escherichia coli, Klebsiella pnuemoniae and Pseudomona saeruginosa with ratios (64%, 12%, 8%, 8%, 4% and 4% ) respectively. The sensitivity and resistance of these isolates to 12 antibiotic were studied, where the Gentamycin appear to be more effective on most of the isolates while all the isolates showed resistance to Nalidixic acid with 100% percent . Also, Plasmid DNA content showed different sizes of DNA bands in four types of these isolates.